Isu-isu semasa dari perspektif Islam (Kuala Lumpur, Malaysia Institut Kefahaman Islam Malaysia, 1999)
Essays on current Malaysian social issues from an Islamic perspective; collection of articles.
Keywords: Islam and social problems -- Malaysia; Malaysia -- Social conditions